In Situ Observation of Room-Temperature Magnesium Metal Deposition on a NASICON/IL Hybrid Solid Electrolyte - Wei, Zhixuan; Singh, Dheeraj Kumar; Helmbrecht, Katharina; Sann, Joachim; Yusim, Yuriy; Kieser, Joy A.; Glaser, Clarissa; Rohnke, Marcus; Groß, Axel; Janek, Jürgen; Justus Liebig University Giessen (My University, 2023)
Secondary batteries using multivalent cations as ionic charge carriers have attracted increasing attention in recent years due to the high theoretical energy density provided by multi-electron redox reactions. However, the high charge density of these cations inevitably leads to sluggish kinetics of ion migration at room temperature, which poses a challenge for the development of solid-state batteries using multivalent ions. Here, a magnesium ion conducting hybrid solid electrolyte (HSE) is prepared, consisting of a new NASICON-structured material, Mg0.5Sn2(PO4)3, and a small amount of magnesium ionic liquid. The HSE shows superior room-temperature ionic conductivity of 1.11 × 10−4 S cm−1 and an activation energy of 0.36 eV. Due to the good compatibility of the HSE with the magnesium metal anode, symmetric MgǀHSEǀMg cells show stable magnesium plating and stripping behavior at room temperature. Using in situ electrochemical scanning electron microscopy measurements, the room temperature growth-induced fracture of the HSE is observed, giving unequivocal evidence for magnesium deposition. These results may serve as a starting point for understanding the magnesium deposition mechanism on solid electrolytes in solid-state batteries.
Keywords: ddc:540